Tanggung Jawab Pemerintah Daerah Terhadap Perkembangan Wisata Alam Fulan Fehan di Kabupaten Belu - Putry Cantika Maharani Sonbay; Saryono Yohanes; Hernimus Ratu Udju (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This study aims to find out and analyze the regional responsibility for the development of fulan fehan natural tourism in Belu Regency. This study is a normative judicial research using a case approach and a conceptual approach that uses primary data in the form of interviews from 30 research respondents and secondary data in the form of primary, secondary and tertiary legal materials. The results of the study show that (1) The influence of infrastructure on the development of fulan fehan natural tourism is very important. Infrastructure that must always be considered so that visitors feel happy and always interested in visiting these tourist attractions such as roads and rest areas. (2) The Belu Regency government's efforts to develop Fulan Fehan natural tourism in Belu Regency are divided into several efforts, namely preventive efforts, repressive efforts, tourism promotion efforts and tourism improvement efforts.